Outcome of mother to infant acquired GBV-C/HGV infection. Issue 1 (1st January 1999) - Zuin, G; Saccani, B; Di Giacomo, S; Tanzi, E; Zanetti, A R; Principi, N
Abstract : Twelve children born to hepatitis C virus antibody GBV-C/HGV RNA positive mothers who acquired GBV-C/HGV infection by the vertical or perinatal route were studied. Most (91%) were persistently GBV-C/HGV RNA positive up to 12 months of age. Four out of six cases who acquired GBV-C/HGV alone had normal alanine amino transferase activities. Long lasting evidence of hepatocellular injury was detected only in children with GBV-C/HGV and hepatitis C virus and HIV coinfection.